2021
DOI: 10.1021/acsami.1c14401
|View full text |Cite
|
Sign up to set email alerts
|

Protein Corona Inhibits Endosomal Escape of Functionalized DNA Nanostructures in Living Cells

Abstract: DNA nanostructures (DNs) can be designed in a controlled and programmable manner, and these structures are increasingly used in a variety of biomedical applications, such as the delivery of therapeutic agents. When exposed to biological liquids, most nanomaterials become covered by a protein corona, which in turn modulates their cellular uptake and the biological response they elicit. However, the interplay between living cells and designed DNs are still not well established. Namely, there are very limited stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 120 publications
0
8
0
Order By: Relevance
“…The type of cell line also plays a vital role in the internalization of DNA nanostructures. Smolková et al have demonstrated the effect of cell size in the internalization of DNA nanostructures where they found linear correlation between cell area and uptake . We studied the uptake of DNs in a panel of cell lines originating from different sources and body tissues including SH-SY5Y, HeLa, SUM159, KB3, and RPe1.…”
Section: Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The type of cell line also plays a vital role in the internalization of DNA nanostructures. Smolková et al have demonstrated the effect of cell size in the internalization of DNA nanostructures where they found linear correlation between cell area and uptake . We studied the uptake of DNs in a panel of cell lines originating from different sources and body tissues including SH-SY5Y, HeLa, SUM159, KB3, and RPe1.…”
Section: Results and Discussionmentioning
confidence: 98%
“…Different fluorophores were excited using different lasers, i.e., for Hoechst 405 nm, Tf-A488:488 nm, TD-Cy3:561 nm, and Gal3-Cy5 633 nm. The image analysis was done using Fiji ImageJ software. ,, The background from each image was subtracted using Fiji ImageJ software (NIH), and whole cell intensity was quantified using maximum intensity projection. The autofluorescence of the cells was eliminated by quantifying the signal from the unlabeled cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For high-quality confocal images and 3D and 4D analysis, we used the brand-new high-resolution spinning disk confocal system IXplore SpinSR (Olympus, Tokyo, Japan). , Cells (HepG2 and Alexander cell lines) were grown in either the monolayer culture (MC) or collagen scaffolds (CSs) under regular culturing conditions, i.e., humidified atmosphere with 5% CO 2 at 37 °C. Afterward, cells were labeled with specific fluorescent probes; see details in Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…Predominantly, the DNA tetrahedron (∼10 nm) is used in these studies but over the last several years larger DNA origami structures (∼100 nm) have become more common, likely due to the availability of more sites to couple biocompatible signaling molecules. We observed that the display of targeting antigens or ligands on the surface of the DNA NS is not a requirement for uptake and that DNA NS with 21,31,46,47 and without 5,34,48,49 targeting moieties have been reported to be internalized by cells. The spatial arrangement of antigens on the DNA NS does, however, perform significantly better in immunostimulatory applications since it leverages B/T-cell receptor antigen pattern recognition and macrophage functionality.…”
Section: Uptake Of Dna Ns Into Mammalian Cellsmentioning
confidence: 92%